Comparison of Connective Tissue Graft and Platelet Rich Fibrin as Matrices in A Novel Papillary Augmentation Access: A Randomized Controlled Clinical Trial - Abirami, T.; Subramanian, Sangeetha; Prakash, P. S.G.; Victor, D. J.; Devapriya, A. M. (European Journal of Dentistry, 2019)
Objective The present study was a randomized controlled clinical trial with the aim of evaluating the increase in papillary height and reduction in black triangle height obtained by the novel papillary augmentation access with either connective tissue graft (CTG) or platelet-rich fibrin (PRF) as matrix from baseline to 6 months.Materials and Methods A total number of 20 sites with Nordland and Tarnow’s Class I, I-II and II interdental papillary loss were recruited into the study. The sites were randomly allocated with 10 sites per group into either: Group A (control group) or Group B (test group) which utilizes the same technique with CTG or PRF as matrix, respectively. The clinical parameters such as PPD (probing pocket depth) and CAL (clinical attachment level) at the surgical site, plaque score (FMPS), bleeding scores (FMBS), interdental papillary height (PH) and black triangle height (BTH), along with visual analog score by dentist (VAS-D) and by patient (VAS-P) were evaluated at baseline and at 6 months.Results In both CTG and PRF groups, all the primary and secondary outcome variables such as PH, BTH, VAS-D and VAS-P showed statistically significant improvement from baseline to 6 months (p ≤0.05) within the group. On comparison at 6 months, there were no differences in the papillary height between the groups. However, the BTH has significantly reduced in the CTG group than the PRF group. Similarly, the VAS-D significantly improved in the CTG group than the PRF group (p = 0.010) at 6 months.Conclusion The study demonstrates that the proposed papillary augmentation access with CTG and PRF was successful in managing the unaesthetic interdental papillary loss, with CTG showing better results in terms of reduction of black triangle than PRF.
Keywords: black triangle; connective tissue graft; interdental papilla; papillary loss; papilla reconstruction; platelet rich fibrin